Konstruksi Hukum QRIS sebagai Perluasan Definisi Mata Uang: Analisis Sinkronisasi Hukum atas Undang-Undang Nomor 7 Tahun 2011 tentang Mata Uang - Putra Arista Pratama; Aullya’wy Ridzky Regitafitri (J-CEKI : Jurnal Cendekia Ilmiah, 2026)
The development of digital payment systems in Indonesia through the Quick Response Code Indonesian Standard (QRIS) has accelerated non-cash transactions and promoted the formation of a cashless society. However, this technological advancement has not been fully accompanied by legal synchronization, particularly between Law Number 7 of 2011 on Currency and Law Number 4 of 2023 on the Development and Strengthening of the Financial Sector (P2SK Law). This study aims to analyze the legal status of QRIS from the perspective of Rupiah monetary sovereignty, consumer protection, and the principles of justice and financial inclusion. This research employs a normative juridical method using statutory and conceptual approaches, examining legislation, legal doctrines, and the practical implementation of QRIS in Indonesia. The analysis is conducted prescriptively to identify legal inconsistencies and propose normative solutions. The findings reveal a significant legal gap concerning the definition of currency and the criminal sanctions applicable to digital transactions. Functionally, QRIS performs the role of money as a means of payment; however, it has not been formally recognized as legal tender with binding legal force equivalent to physical Rupiah under the Currency Law. This condition creates legal uncertainty in consumer protection, particularly in cases of system failures that result in financial losses. Moreover, the implementation of cashless-only transactions potentially violates the obligation to accept Rupiah and may lead to discrimination against unbanked populations and communities in remote and underdeveloped areas. This study concludes that amendments to the Currency Law and regulatory harmonization are urgently needed to formally recognize Digital Rupiah, strengthen legal protection for consumers, and ensure that the digitalization of payment systems remains consistent with the principles of monetary sovereignty, social justice, and financial inclusivity